Case report: One pediatric liver-transplant recipient with SARS-CoV-2 infection suffering unexplained mixed acidosis - Yu, Lianhu; Zheng, Lu; Hu, Hui; Wan, Ping; Lu, Yanming; Wang, Libo; Yu, Hui; Chen, Yiwei; Zhou, Jianguo; Xia, Qiang; Zhou, Wenhao; Zhang, Ting (Frontiers in Medicine, 2023)
Immunosuppressants (IS) are key therapy agents after liver transplant with various side effects. Calcineurin inhibitor (CNI) may lead to metabolic acidosis while mycophenolate mofetil (MMF) showed rare nephrotoxicity. During COVID-19 pandemic, the management for post-liver transplant patient is challenging, especially when dealing with drug side effects. A girl was admitted to our hospital due to SARS-CoV-2 infection 3 months after liver transplant. During hospitalization, blood gas analysis showed severe mixed acidosis. Liquid replacement therapy and decreased CsA dose cannot improve the condition while withdrawing MMF is effective. The girl’s mixed acidosis cannot be explained by Nieman-Pick disease and SARS-CoV-2 infection. CNIs could cause metabolic acidosis but declining the dose of CsA didn’t improve her acidosis while withdrawing MMF showed a good effect. Together with the Naranjo Scale result, we suspect that acidosis maybe a rare side effect of MMF.